The Relationship Between Menopause and Dysphagia: A Scoping Review - Charles Lenell; Rodolfo Pe?a-Ch?vez; Ryan J. Burdick; Nicole Rogus-Pulia (Mary Ann Liebert, 2022)
Purpose: Menopause marks the end of fertility and rapid decline of ovarian hormones in the female body, which corresponds to a myriad of changes to bodily systems, including the upper aerodigestive tract. Despite substantial evidence that menopause negatively impacts oral health, bones, and skeletal muscles, little research has examined these effects as they relate to swallowing. The purpose of this scoping review was to compile and summarize the existing literature investigating the relationship between menopause and swallowing-related structures and physiology. Methods: Search terms were selected for three databases (PubMed, Scopus, and CINAHL) to gather relevant literature evaluating the relationship between menopause and swallowing-related anatomy as well as swallowing functions in both human and animal models. Relevant articles were reviewed, collated, and summarized to synthesize findings, identify gaps in the literature, and provide suggestions for future directions. Results: This scoping review yielded 204 studies with the majority of these studies relating to one or more of the following categories: oral health, saliva, mandibular structures, and taste. Common oral symptoms reported in the literature included xerostomia, hyposalivation, tooth decay, inflammation of oral mucosa, and oral pain. Although literature supports that menopause adversely affects oral health, saliva, mandibular structures, and alters taste, a dearth of information was evident regarding how these hormone-dependent changes can adversely affect swallowing. Conclusions: The relationship between menopause and swallowing has been overlooked by field of speech?language pathology. By identifying the major gaps in the literature, these results will inform future investigations evaluating relationships among ovarian hormones and swallowing.